2004
DOI: 10.1159/000078559
|View full text |Cite
|
Sign up to set email alerts
|

The most common chromosome aberration detected by high-resolution comparative genomic hybridization in vulvar intraepithelial neoplasia is not seen in vulvar squamous cell carcinoma

Abstract: We analyzed genetic changes in condylomas (four cases), vulvar intraepithelial neoplasia I–III (VIN I–III, eleven cases), and primary vulvar squamous cell carcinomas (VSCC, ten cases) by high-resolution comparative genomic hybridization (HR-CGH) and flowcytometry. All samples were also human papilloma virus (HPV)-genotyped. Gain of chromosome 1, the aberration most often seen in VIN III (67%), was not seen in HPV-positive or -negative VSCCs (0%). Both VIN III and VSCC frequently showed gain of 3q (56 and 70%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
3
5
0
Order By: Relevance
“…Particularly, gain of the complete chromosome 1 was significantly associated with the development of VSCC. Similar to our observation, Bryndorf et al and Purdie et al also found that HPV‐positive VIN lesions frequently exhibited gains of chromosome 1pq, whereas this was not the case for carcinomas. Based on this observation it has been suggested that these VIN lesions are unlikely to represent direct precursors of VSCC .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Particularly, gain of the complete chromosome 1 was significantly associated with the development of VSCC. Similar to our observation, Bryndorf et al and Purdie et al also found that HPV‐positive VIN lesions frequently exhibited gains of chromosome 1pq, whereas this was not the case for carcinomas. Based on this observation it has been suggested that these VIN lesions are unlikely to represent direct precursors of VSCC .…”
Section: Discussionsupporting
confidence: 92%
“…HPV‐positive VIN VSCC frequently showed chromosome 1 gains (discussed below), chromosome 3q gain, chromosome 4 loss and chromosome 20 gain. In agreement with this, 2 previous studies on HPV‐positive VIN lesions demonstrated frequent gains at chromosome 1pq, 3q, 19, and/or 20q . Gains of chromosome 1pq, 3q, and 20q were also common in HPV‐positive anal intraepithelial neoplasia .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Gains of 20q are very common in lymphoid malignancies as well as in epithelial cancers (Joos et al, 2002(Joos et al, , 2003Garcia et al, 2003;Hurst et al, 2004;Kimura et al, 2004). Gains of 22q were also detected in noninvasive in situ neoplasia, indicating that it may be a primary or at least early genetic event in neoplastic transformation (Bryndorf et al, 2004). However, it is not specific for PTCL or lymphoma at all.…”
Section: Discussionmentioning
confidence: 99%